Taking the Pulse: perceptions of crime trends and community safety and support for crime control methods in the Canadian Prairies - Ian V. McPhail; Mark E. Olver; Carolyn Brooks (Journal of Community Safety and Well-Being, 2017)
The present study analyzed crime survey data extracted from the 2012 Saskatchewan Taking the Pulse survey on a sample of 1,700 adult Saskatchewan residents. The focus was on examining perceptions of crime trends, perceived effectiveness of various methods for controlling crime, and their sociodemographic correlates. The majority of survey respondents perceived crime in general to be on the rise (37%) or to have not changed at all (48%) over the last three years. Individuals who perceived crime to have decreased were significantly more likely to support alternatives to punishment as effective methods for reducing crime, while individuals who perceived crime to be on the rise were twice as likely to support the use of punitive methods. Perceptions of community safety were unrelated to preference for one crime reduction method over another. Education level was inversely related to crime trend perceptions (r = -.14) and preference for punitive methods to reduce crime (r = -.20). Finally, the results of logistic regression indicated higher levels of education, higher income, and perceptions of crime decreasing were all uniquely associated with a preference for alternatives to punishment in reducing crime. In these analyses, younger age was predictive of a preference for alternatives in reducing youth crime, while urban residential setting was associated with a preference for alternatives to punishment in reducing crime in general.